Gender-Based Evaluation of IASTM and Dry Needling Therapy on Spasticity and Pain in Neurological Patients: A 12-Month Experimental Study - Malvi, Ruchit; Lohar, Deepak; Khan, Jafar; Aggarwal, Kapil; Menria, Shubham; Balala, Deepika; Pal, Renuka; Qureshi, Abid R; Choubisa, Chitrakshi A; Rawal, Hardik (Journal of Neonatal Surgery, 2025)
Background: Spasticity and pain frequently affect neurological patients, limiting function and quality of life. This study evaluated the gender-based effectiveness of combining Instrument-Assisted Soft Tissue Mobilization (IASTM) and dry needling therapy. Pre- and post-treatment assessments using the Modified Ashworth Scale (MAS) and Visual Analogue Scale (VAS) showed significant reductions in spasticity and pain, demonstrating the therapeutic potential of this combined intervention. Methodology: A 12-month Gender based experimental study was carried on total of 60 neurological patients (≥40 years old) who had spasticity in neurological disorders had IASTM and dry needling therapy three times a week for 45 minutes each session for 2.5 months. VAS and MAS were used to measure pain and spasticity. Results: The mean MAS and VAS scores significantly decreased after treatment in both genders. In males, MAS reduced from 1.66 to 1.07 and VAS from 6.48 to 3.33. In females, MAS decreased from 1.71 to 1.11 and VAS from 6.58 to 3.41, indicating treatment effectiveness. Conclusion: The study supports IASTM and dry needling as effective therapies, warranting broader trials and long-term follow-up for validation